(3TQM GdTGajIs - (3Qcf GdOjf CHh eMeO GdMSf Hf eMeO GdGSJQGHGOis; (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS, CHh YeQh LeGd GdOjf GHf GdMGLH,J (B646 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg Ydi JhGdi fYeg hfhGdg abO EdJeS efi LeGYI Cf CTQM GdebOeI ai GdJUQja GdefShH Edi LeGd GdOjf CHj YeQh YKeGf TQMkG Sgd bhdg GdJUQja Yde HCUhd JYQa Hge CMhGd CHfjg Gdcde s
(3BNQgG (B:s
(3hCeG cJGHI Hdi HGdjGA adbhI EeGdJgG hESJbdGd GdEeGdI ai GdOdGdI Ydi GdjGA ZGdHkG hGddg CYde JeJ HMeO Gddg hMSf Jhajbg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs